Diagnostic performance of the E6/E7 mRNA-based Optimygene HR-HPV RT-qDx assay for cervical cancer screening - Hye-young Wang; Hyunil Kim; Kwang Hwa Park (International Journal of Infectious Diseases, 2019)
Objectives: Pap smear and high-risk human papillomavirus (HR-HPV) DNA testing are the most widely applied methods for cervical cancer screening, but both methods are limited by their low specificity and lack of association with patient prognoses. The aim of this study was to compare the clinical and prognostic significance of HPV E6/E7 mRNA as an early biomarker with cytology and HPV DNA detection in cervical cancer screening. Methods: This study evaluated the performance of the Optimygene HR-HPV RT-qDx assay, which is an HPV E6/E7 mRNA-based assay, to detect 16 HR-HPV subtypes: HPV 16, 18, 31, 33, 35, 39, 45, 51, 52, 53, 56, 58, 59, 66, 68, and 69. The clinical evaluation was conducted using 563 ThinPrep liquid-based cytology samples and the results were compared to those of cytological and histological diagnoses and HPV DNA testing. Results: The clinical sensitivity and specificity of the Optimygene HR-HPV RT-qDx assay for the detection of high-grade lesions, according to cervical cytology, were 92.4% (95% confidence interval (CI) 0.9167–0.9972, p < 0.0001) and 96.9% (95% CI 0.8632–0.9524, p < 0.0001), respectively; they were 85.9% (95% CI 0.7631–0.9211, p < 0.0001) and 82.5% (95% CI 0.7491–0.8825, p < 0.0001), respectively, for CIN2+. This assay showed a higher specificity and positive predictive value for cytological and histological diagnosis than HPV DNA testing. Overall, the agreement between the Optimygene HR-HPV RT-qDx assay and HPV DNA testing in cytological and histological diagnosis was 87.9% (κ = 0.76, 95% CI 0.7054–0.8128, p < 0.0001) and 90.5% (k = 0.81, 95% CI 0.7338–0.8878, p < 0.0001), respectively. In this study, the most frequently detected HPV genotypes among HR-HPV-positive women were HPV 16 (37.9%), HPV 33–58 (21.5%), and HPV 18 (11.4%). Conclusions: These findings suggest that the higher specificity and positive predictive value of the Optimygene HR-HPV RT-qDx assay are valuable for predicting insignificant HPV DNA infections among patients with a borderline cytological diagnosis. This assay could be used to prevent unnecessary biopsy procedures and the over-referral of patients with transient HPV infections, as well as reduce patient anxiety during the follow-up period. Keywords: Cervical cancer, Human papillomavirus, E6/E7 mRNA, DNA, Reverse transcriptase quantitative PCR, Molecular diagnosis